Physical oceanography during POSEIDON cruise POS470 in Madeira basin in May/June 2014 - Joanna J Waniek; Helena C Frazão; Robert Mars (PANGAEA, 2022)
During the cruise POS470 on board the German R/V Poseidon, we measured temperature, salinity, dissolved oxygen, fluorescence and turbidity on 33 stations in the Madeira Basin, Northeast Atlantic in May and June 2014. We aimed to study the physical and biogeochemical conditions in the upper 2000 m of the water column in the catchment area of Kiel 276. The CTD stations are distributed along three meridians (23°W, 22°W, and 21°W) and between 30° and 37°N to locate the Azores Front. The dissolved oxygen data is noisy below 1700 m. Since there was no measurement of dissolved oxygen (Winkler titration) during the cruise, the data cannot be calibrated.